Caveolin-1 function at the plasma membrane and in intracellular compartments in cancer - Simón, L.; Campos, A.; Leyton, L.; Quest, A. F. G. (Cancer and metastasis reviews, 2020)
Caveolin-1 (CAV1) is commonly considered to function as a cell surface protein, for instance in the genesis of caveolae. Nonetheless, it is also present in many intracellular organelles and compartments. The contributions of these intracellular pools to CAV1 function are generally less well understood, and this is also the case in the context of cancer. This review will summarize literature available on the role of CAV1 in cancer, highlighting particularly our understanding of the canonical (CAV1 in the plasma membrane) and non-canonical pathways (CAV1 in organelles and exosomes) linked to the dual role of the protein as a tumor suppressor and promoter of metastasis. With this in mind, we will focus on recently emerging concepts linking CAV1 function to the regulation of intracellular organelle communication within the same cell where CAV1 is expressed. However, we now know that CAV1 can be released from cells in exosomes and generate systemic effects. Thus, we will also elaborate on how CAV1 participates in intracellular communication between organelles as well as signaling between cells (non-canonical pathways) in cancer.